Application of sugar-containing biomass: one-step synthesis of 2-furylglyoxylic acid and its derivatives from a vitamin C precursor. Issue 5 (25th February 2022) - Chen, Jiao; Zhu, Zhenhua; Cai, Jiali; Cao, Mengru; Sha, Feng; Tao, Sha; Yang, Hao; Gan, Haifeng; Wu, Hongli; Cao, Fei; Zhao, Lili; Ouyang, Pingkai
Abstract : A novel pathway is demonstrated for preparing the high-value pharmaceutical intermediate 2-furylglyoxylic acid from 2-keto-l -gulonic acid, a bio-based sugar acid, via dehydration. Abstract : We developed a novel pathway for preparing the high-value pharmaceutical intermediate 2-furylglyoxylic acid (2FGA) from 2-keto-l -gulonic acid (2KGA), a bio-based sugar-acid monomer and precursor of vitamin C, via dehydration. 100 g L −1 methyl 2-keto-l -gulonicate (Me-2KGA) was transformed into methyl 2-furylglyoxylicate (Me-2FGA) with a maximum yield of 79.4%, competing with the yields obtained via traditional commercial synthesis methods. Subsequently, characterisation methods and theoretical calculations were employed; it was confirmed that natural 2KGA, with a 2, 5-cyclic configuration, was esterified initially, it then underwent a transformation to an opened intermediate which further recyclized in a 3, 6-cyclic configuration via removing one molecule of water, and this was finally dehydrated to Me-2FGA. This study offers novel insight into the flexibility and versatility of furan-based compounds.